TelenursaMoms: A Digital Mental Health Service Innovation for Postpartum Mothers with Neglectful Family Challenges - Ekasari, Rizqiana Dita; Satiti, Ika Arum Dewi; Wahyuningrum, Ari Damayanti (Majalah Kesehatan Indonesia, 2025)
Postpartum anxiety and depression are common mental health problems in postpartum mothers, especially when there is a challenge of low family support (neglectful family). Postpartum mothers who are neglected by their families are 20% more at risk of experiencing anxiety and 13% more at risk of experiencing postpartum depression compared to mothers who receive family care. Suboptimal family support can exacerbate psychological symptoms and hinder mother-infant bonding. The purpose of this study was to develop the TelenursaMoms application, a digital platform that is easily accessible at any time to assess family function and maternal psychological health, as well as provide initial management for postpartum mothers with neglectful challenges. The study used a quasi-experimental pre-post test with a control group design with 80 postpartum mothers who met the inclusion criteria. The instruments used were the Family Functioning and Cohesion Scale (FFCS) and the Postpartum Mother Assessment Tool (ASIPP). Data analysis used ANCOVA. After adjusting for pre-test scores, ANCOVA showed that the TelenursaMoms intervention group had significantly higher post-test scores than the control group in all outcomes: emotional regulation (F(1,79) = 16.0, p < 0.001, partial η² = 0.17), maternal self-confidence (F(1,79) = 19.5, p < 0.001, partial η² = 0.20), marital satisfaction (F(1,79) = 25.0, p < 0.001, partial η² = 0.24), and family cohesion (F(1,79) = 42.3, p < 0.001, partial η² = 0.35). TelenursaMoms proved significantly effective, especially in strengthening family cohesion and marital satisfaction, two relational aspects that are frequently neglected in existing digital interventions for maternal well-being.